2022
DOI: 10.3390/sym14020345
|View full text |Cite
|
Sign up to set email alerts
|

From Hemispheric Asymmetry through Sensorimotor Experiences to Cognitive Outcomes in Children with Cerebral Palsy

Abstract: Recent neuroimaging studies allowed us to explore abnormal brain structures and interhemispheric connectivity in children with cerebral palsy (CP). Behavioral researchers have long reported that children with CP exhibit suboptimal performance in different cognitive domains (e.g., receptive and expressive language skills, reading, mental imagery, spatial processing, subitizing, math, and executive functions). However, there has been very limited cross-domain research involving these two areas of scientific inqu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 558 publications
(778 reference statements)
0
4
0
Order By: Relevance
“…Environmental affordances can be manipulated in the form of subtraction or addition. Examples of the subtraction in environmental affordances would be forced-use therapy (FUT [86,87]), constraint-induced movement therapy (CIMT [63,[88][89][90]), or interventions using a novel PlaySkin Duo TM (Move 2 Learn Innovation Lab, Department of Physical Therapy, University of Delaware, Newark, DE, USA) soft exoskeletal garment (PlaySkin Duo [10]). In FUT and CIMT therapies, the child's better functioning hand is casted, thus significantly preventing its use, especially for activities requiring fine-motor movements.…”
Section: Environmental Affordances Might Affect Children's Hand Usementioning
confidence: 99%
See 1 more Smart Citation
“…Environmental affordances can be manipulated in the form of subtraction or addition. Examples of the subtraction in environmental affordances would be forced-use therapy (FUT [86,87]), constraint-induced movement therapy (CIMT [63,[88][89][90]), or interventions using a novel PlaySkin Duo TM (Move 2 Learn Innovation Lab, Department of Physical Therapy, University of Delaware, Newark, DE, USA) soft exoskeletal garment (PlaySkin Duo [10]). In FUT and CIMT therapies, the child's better functioning hand is casted, thus significantly preventing its use, especially for activities requiring fine-motor movements.…”
Section: Environmental Affordances Might Affect Children's Hand Usementioning
confidence: 99%
“…Hemispheric lateralization increases the efficiency of information processing through parallel processing, redundancy reduction, and interhemispheric conflict prevention [7][8][9]. If hand preference is a marker of hemispheric lateralization, a stronger hand-use preference should result in better developmental outcomes [10]. Indeed, previous research found that early development of distinct and consistent hand preferences (irrespective of their direction-right or left) might stimulate children's object Symmetry 2023, 15, 2161 2 of 18 management (i.e., object storage [11]), object construction (i.e., block stacking onset and skill level [12]), tool-use [13], language skills [14][15][16][17], and cognition [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Specialization of functions across the two hemispheres, along with communication between the hemispheres through the corpus callosum (the corpus callosum is the major commissural tract connecting the cerebral hemispheres and allowing for the coordination and integration of sensorimotor information to optimize information processing [4,5]), ensures more effective information processing and the emergence of new skills [6][7][8][9]. The gains in the speed and quality of information processing provided by hemispheric lateralization may translate into more advanced manual performance [10]. Due to reciprocal relations between early sensorimotor experiences and hemispheric organization, infants with a distinct hand preference are likely to differ from their peers without a hand preference in their patterns of hemispheric lateralization, sensorimotor experiences, and levels of manual performance [11].…”
Section: Introductionmentioning
confidence: 99%
“…These changes occur in an age-related manner and involve both short-range and long-range connections [ 11 , 12 ]. This developmental remodeling of brain connectivity, often referred to as pruning and strengthening of network connectivity, contributes to hemispheric specialization, increased efficiency, and reduced redundancy in neural processes [ 13 - 15 ]. However, disruptions in these processes can contribute to the emergence of cognitive and behavioral impairments observed in individuals with DD [ 16 - 18 ].…”
Section: Introductionmentioning
confidence: 99%